PERAN STRATEGIS BMT DALAM MENDUKUNG KEBERLANJUTAN PROGRAM PENGENTASAN KEMISKINAN: TINJAUAN MODEL DAN DAMPAK - Alfian, Annisa Maulidia; Wira, Ahmad; Hendra, Testru; Duhriah, Duhriah (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to analyze the role of Baitul Maal wat Tamwil (BMT) as an Islamic Microfinance Institution (IMFI) in supporting the sustainability of poverty alleviation in Indonesia. The analysis highlights the strategic function of BMT in empowering microeconomic activities based on Islamic principles, especially for the poor and micro-entrepreneurs who are underserved by conventional financial institutions. Using a literature review approach and synthesis of empirical findings from various studies, this research concludes that BMT significantly contributes to increasing household income, expanding access to Islamic financing, and fostering community-based economic development. However, the sustainability of BMT’s role depends heavily on sharia compliance, technological innovation, and institutional governance quality. Therefore, collaboration between government, BMT, and zakat institutions is essential to optimize the socio-economic impact. This study recommends strengthening human resources, digitalizing services, and conducting periodic evaluations to ensure the effectiveness and sustainability of Islamic microfinance in alleviating poverty.